Policy Implications On The Changes On The Pancasila Economic System Across Three Administrative Periods - Fitri, Tin Amalia (Universitas Islam Negeri Raden Intan Lampung, 2023)
Indonesia has a unique political economy system, called the Pancasila democratic economic system. This system is clearly stated in the state constitution of the 1945 constitution, explaining how the state should regulate the state economy by dividing it into two systems: the top-up level and the bottom-up level. The top up-level is the control of strategic economic sectors by the state, but the management can be handed over to the private sector and hereinafter referred to as state-owned enterprises, this principle is intended to prevent the state of Indonesia from entering the free-market system because it is not in accordance with the principle of justice for the Indonesian nation. The bottom-up level is the management of the microeconomics sector by the community at the village level based on the characteristics of each village. However, in each regime, the economic system that is run is different from the principles of the Pancasila economic democracy system. The implementation of the principles of the economic system implemented in Indonesia is seen from the relevant laws and regulations and the implicit implications of the Indonesian state's political economy policies which form the basis of state economic management and legislators' understanding of the Pancasila democratic economic system are visible. This study uses content analysis and statistical analysis to measure legislators' understanding. The results of the study show that the laws produced by legislators do not support the implementation of the Pancasila democratic economic system and the legislator's understanding of the principles of the Pancasila democratic economic system is low.